Co-ownership as a Solution to Commingling: A Finnish Perspective - Juutilainen, Teemu; Kaisto, Janne (Wolters Kluwer, 2026)
This article studies the effect of commingling on ownership relations, and in particular co-ownership as a solution to these situations. The focus is first on tangible movables, but broadens to objects such as bank money, book entries, and virtual currencies. These intangible objects are account-based assets, or can be understood as such. The first part of the analysis takes place at the level of general legal ideas, while the second part examines Finnish law in more detail. Both parts involve comparative observations. The analysis suggests that co-ownership is generally a rationally justifiable solution and should therefore be widely applicable. However, its relative merits depend on the broader legal context, and thus vary between legal systems. The scope of co-ownership as a solution to commingling is currently unclear under Finnish law. Especially as regards account-based assets, the case law of the Finnish Supreme Court excludes this solution in certain situations where its adoption would otherwise be advisable.